2016
DOI: 10.15419/bmrat.v3i11.136
|View full text |Cite
|
Sign up to set email alerts
|

The effects of transplanted cells in stem cell therapy for myocardial ischemia

Abstract: It is known that myocardial infarction (MI) causes damages to the heart tissue and that present medical therapies, such as medication, stenting and coronary artery bypass surgery, cannot recover the injured heart. Fortunately, advances in stem cell research have brought hope of full heart recovery for myocardial ischemia patients. There have been many studies using cell therapies for myocardial ischemia, from preclinical trials to clinical trials. However, the biggest concern is the effect of transplanted cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…In addition to increased cell viability, this study showed that preconditioning by celastrol also increases MSC paracrine function. This key feature for effective cell therapy has involved proangiogenic, anti-inflammatory, and antiapoptotic cytokines [ 17 , 47 ]. In the case of ischemic diseases, proangiogenic paracrine activities contribute to wound healing by initiating cell proliferation, migration, and maturation for tissue revascularization [ 13 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increased cell viability, this study showed that preconditioning by celastrol also increases MSC paracrine function. This key feature for effective cell therapy has involved proangiogenic, anti-inflammatory, and antiapoptotic cytokines [ 17 , 47 ]. In the case of ischemic diseases, proangiogenic paracrine activities contribute to wound healing by initiating cell proliferation, migration, and maturation for tissue revascularization [ 13 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%